Augmented phytotoxic effect of nanoencapsulated ophiobolin A. Issue 5 (4th March 2022) - Vurro, Maurizio; Townley, Helen E.; Morrison, Rachel; Boari, Angela; Masi, Marco; Evidente, Antonio
Abstract: Ophiobolin A is a secondary phytotoxic metabolite produced by some pathogenic fungal species responsible for severe plant diseases, considered to play a role in disease development and symptom appearance. Herein we investigated whether the phytotoxic activities of ophiobolin A against weed species could be improved by nanoencapsulation. Given the rapid natural degradation of the compound, it was hoped that nanoencapsulation would prolong the phytotoxic effects or enhance the bioactivity, thus leading to improved weed control capabilities. This article presents an assessment of the effectiveness of encapsulated ophiobolin A on 11 commonly found weed species, compared to the pure ophiobolin, to the particle alone, and a combination of mixed particles and ophiobolin A, by applying the solution droplets to both intact or injured leaf surface, on the adaxial or abaxial side. The bioassays showed the improved efficacy of the encapsulated ophiobolin, and the need for leaf lesions to diffuse the particles into the tissues.